Refractory Headaches - Begasse de Dhaem, Olivia; Rizzoli, Paul (Seminars in Neurology, 2022)
Medication overuse headache (MOH), new daily persistent headache (NDPH), and persistent refractory headache attributed to severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) infection represent a significant burden in terms of disability and quality of life, and a challenge in terms of definition, pathophysiology, and treatment. Regarding MOH, prevention without withdrawal is not inferior to prevention with withdrawal. Preventive medications like topiramate, onabotulinumtoxinA, and calcitonin gene-related peptide (CGRP) monoclonal antibodies improve chronic migraine with MOH regardless of withdrawal. The differential diagnosis of NDPH is broad and should be carefully examined. There are no guidelines for the treatment of NDPH, but options include a short course of steroids, nerve blocks, topiramate, nortriptyline, gabapentin, CGRP monoclonal antibodies, and onabotulinumtoxinA. The persistence of headache 3 months after SARS-CoV2 infection is a predictor of poor prognosis.
Keywords: new daily persistent headache; medication overuse headache; medication adaptation headache; chronic refractory headache attributed to SARS-CoV2 infection